Phase structure of two-flavor QCD at finite chemical potential - Braun, Jens; Haas, Lisa Marie; Marhauser, Florian; Pawlowski, Jan M. (Physical review letters, 2011)
We study the phase diagram of two-flavor QCD at imaginary chemical potentials in the chiral limit. To this end we compute order parameters for chiral symmetry breaking and quark confinement. The interrelation of quark confinement and chiral symmetry breaking is analyzed with a new order parameter for the confinement phase transition. We show that it is directly related to both the quark density as well as the Polyakov loop expectation value. Our analytical and numerical results suggest a close relation between the chiral and the confinement phase transition.